A “Cultura de Si” em Foucault - FREITAS, Frank Alexandre Rosa (Universidade Federal do Pará, 2018)
Based on the recent works of Michel Foucault, we face a significant turning point in his philosophy, through the study of the Greek notion of care of the self. That notion, according to Pierre Hadot, would have been attracted by some aspects of his approach to ancient philosophy as spiritual exercises. From this new perspective Foucault thinks the subject who builds himself with exercises, practices and techniques of himself. Consequently, this dissertation aims to analyze “The Culture of the Self”, that is extensively worked and researched by Foucault, in his last works and mainly from The Hermeneutics of The Subject, a 1982 course; besides the History of Sexuality II and III, and other related texts to the aspects of old ethics. Thus, we start from the Foucault’s analysis of The Culture of the Self to the convergences and divergences critically undertaken by Hadot. Finally, we can arrive in chapter III of our dissertation, to understand how Foucault analyzes The Culture of the Self after the course of 1982. What changes in the later courses. What changes in the last two volumes of the History of Sexuality in relation to the Hermeneutics of the Subject. Also, the question of the actuality of The Culture of the Self and its relation to the current social practices for the possibility of an aesthetic of existence is another object of investigation. We then turn to the question of whether or not Foucault would propose to re-evaluate an ancient ethic, in order to reflect about the ways in which is possible to understand, through the look he has given to antiquity, an art of living.